Subacute cognitive impairment after first-ever transient ischemic attack or ischemic stroke in young adults: The ODYSSEY study. (March 2023) - Schellekens, Mijntje MI; Boot, Esther M; Verhoeven, Jamie I; Ekker, Merel S; van Alebeek, Mayte E; Brouwers, Paul JAM; Arntz, Renate M; van Dijk, Gert W; Gons, Rob AR; van Uden, Inge WM; den Heijer, Tom; de Kort, Paul LM; et al.
Introduction: We aimed to investigate the prevalence of cognitive impairment in the subacute phase after transient ischemic attack (TIA) and ischemic stroke (IS), factors associated with a vascular cognitive disorder, and the prevalence of subjective cognitive complaints and their relation with objective cognitive performance. Patients and methods: In this multicenter prospective cohort study, we recruited patients with first-ever TIA and IS, aged 18–49 years, between 2013 and 2021 for cognitive assessment up to 6 months after index event. We calculated composite Z-scores for seven cognitive domains. We defined cognitive impairment as a composite Z-score < −1.5. We defined major vascular cognitive disorder as a Z-score < −2.0 in one or more cognitive domains. Results: Fifty three TIA and 545 IS patients completed cognitive assessment with mean time to assessment of 89.7 (SD 40.7) days. The median NIHSS at admission was 3 (interquartile range, 1–5). Cognitive impairment was common in five domains (up to 37%), with similar proportion in TIA and IS patients. Patients with major vascular cognitive disorder had a lower education level, higher NIHSS scores and more frequent lesions in the left frontotemporal lobe than without vascular cognitive disorder ( p  < 0.05 FDR-corrected). Subjective memory and executive cognitive complaints were present in about two-thirds of the patients, but were weakly associated with objective cognitive performance (β: −0.32 and −0.21, respectively). Discussion and conclusion: In the subacute phase after TIA or stroke in young adults, cognitive impairment and subjective cognitive complaints are prevalent, but they are weakly associated with each other.